Numerical Simulation Study on the Development Characteristics of the "Two Zones" in the Overlying Strata of the 13050 Working Face in Yunding Coal Industry - Zhang, Chuanliang (International Journal of Natural Resources and Environmental Studies, 2026)
To accurately grasp the failure pattern of the overlying strata under the conditions of top-coal caving mining in the thick coal seam of the 13050 working face at Yunding Coal Industry, a systematic study was conducted on the development height and distribution characteristics of the "three zones" (caved zone, water-conducting fracture zone) in the overlying strata. This study was based on the geological and mining conditions of the working face and utilized a combination of theoretical calculations, downhole borehole television measurements, and 3DEC numerical simulation. The results show that the theoretical calculation yielded a caved zone height of 10.48–14.88 m and a water-conducting fracture zone height of 39.77–58.83 m. The field measurements indicated a caved zone height of 12.93–20.21 m and a water-conducting fracture zone height of 38.79–60.63 m. The numerical simulation showed a maximum water-conducting fracture zone height of approximately 43.9 m. The results from the three methods exhibit a high degree of agreement. Consequently, the caved zone height for this working face is determined to be 13–16 m, and the water-conducting fracture zone height is determined to be 40–44 m. This can provide a reliable basis for roof control, the design of waterproof coal/rock pillars, and safe mining operations at the working face.